EVALUASI KERUSAKAN KAWASAN KARST DI KABUPATEN MUNA Studi Kasus Kecamatan Lohia Dan Kecamatan Bone - , LAODE MUHAMAD GUNAWAN MUSAWARI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Karst area is one of landscapes that have potency and ecological functions in maintaining the balance of nature and human existence who live in it. The growth of population results the increase of intensity in natural resources utilization. Karst area that provides natural resources for the fulfillment of human needs will be damaged if its utilization is highest. High or low levels of damage to karst area both in densely populated area or not can be known through evaluation of damage to karst area. This research is aimed to 1). Study characteristic of damage to karst area in sub-district of Lohia and Bone. 2). Analyze the cause of damage to karst area in sub-district of Lohia and Bone. The method of research used in evaluation of damage to karst area in Muna Regency is method of surveys, interviews and scoring towards determining parameters of damage to karst area. These parameters include the extent of vegetation cover and rock outcrop obtained from data of Citra SPOT 4, fluctuation of spring debit, quality of spring water, and condition of cave biodiversity known from field data and interviews. The results of data analysis in Citra SPOT 4, field and scoring data on determining parameters of damage indicate that Sub-district of Lohia and Bone characterize the development of tropical and shape of topography to karst area in Sub-district of Lohia is transition karst, while Sub-district of Bone characterizes merokarst characteristics. Based on the criteria of parameters in determining damage to karst area, Sub-district of Lohia is classified in minor damage proved by a scoring value of 17 consisted of the value of 3 (three) to the extent of vegetation cover, 1 (one) to condition of rock outcrop, 5 (five) to quality of spring water, 5 (five) to quantity of spring water and 5 (five) to value of condition in cave biodiversity. The damage of karst area in Lohia is caused by the activity of limestone mining, taking from the stalactite and stalagmite of cave, and migratory farming systems while in Bone it is caused by migratory farming systems also.